"Nothing happens in a vacuum here": university-industry collaboration in Iceland. (13th November 2021) - Karlsdottir, Verena; Edvardsson, Ingi Runar; Heijstra, Thamar M.
In recent years, universities have become driving forces of economic growth, and they have taken greater responsibility in economic, cultural, and social matters. Thereby, universities have placed a stronger emphasis on university-industry collaboration (UIC), which facilitates knowledge and technology transfer and frames teaching and research activities. In this article Iceland is an example to illustrate the importance of the triple helix which serves the purpose of enhancing formal UIC. The study conducts a thematic analysis of qualitative data collected in interviews with staff in universities, public research organisations, and companies. The findings show that informal modes of collaboration were prevalent and characterised by short-term orientation and reliance on social capital. The reasons for these findings could be traced to the business culture, funding structures, and the location and size of organisations in Iceland. Based on our findings, we provide recommendations to governments, universities, and industries for strengthening their collaboration.